(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To report a detailed clinical case of an ectopic parathyroid adenoma located in the mediastinum, which was diagnosed based on computed tomography and parathyroid scintigraphy. This case contributes to the scientific literature and shares clinical experience regarding the diagnostic and therapeutic process. Case report: A 65-year-old female patient presented with symptoms of bone pain. Biochemical investigations revealed severe hypercalcemia and an elevated parathyroid hormone level, establishing the diagnosis of primary hyperparathyroidism. However, initial cervical ultrasound and computed tomography failed to identify any pathology in the normal location of the parathyroid glands. Parathyroid scintigraphy with Technetium-99m Sestamibi and a chest computed tomography scan showed a mass in the superior mediastinum. The patient was underwent surgical resection of a 4 × 2 × 1 cm tumor via sternotomy. Histopathological examination confirmed the mass to be a parathyroid adenoma. The postoperative parathyroid hormone level decreaseed more than 50% from the preoperative baseline confirmed the resection of the parathyroid tumor. Discussion: Regarding the challenges in diagnosing and locating ectopic parathyroid tumors, the role of imaging modalities, such as ultrasound and computed tomography, especially parathyroid scintigraphy in establishing a definitive diagnosis. Conclusion: Summarizing the insights from the case report and discussion, the conclusion emphasizes the critical importance of diagnosing primary hyperparathyroidism caused by a mediastinal ectopic parathyroid adenoma. This leads to the formulation of an accurate and effective treatment strategy.